2020
DOI: 10.1038/s41467-020-18749-2
|View full text |Cite
|
Sign up to set email alerts
|

Versatile direct-writing of dopants in a solid state host through recoil implantation

Abstract: Modifying material properties at the nanoscale is crucially important for devices in nano-electronics, nanophotonics and quantum information. Optically active defects in wide band gap materials, for instance, are critical constituents for the realisation of quantum technologies. Here, we demonstrate the use of recoil implantation, a method exploiting momentum transfer from accelerated ions, for versatile and mask-free material doping. As a proof of concept, we direct-write arrays of optically active defects in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
(55 reference statements)
3
14
0
2
Order By: Relevance
“…𝜏 yields an estimation of the excited state lifetime of a florescent structure at a low excitation power 47 . The excited state lifetime of the observed single PbV center was estimated to be ~3.7 ns, which is consistent with another experimental result 31 . The fluorescence intensity is measured as a function of the excitation laser power, as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…𝜏 yields an estimation of the excited state lifetime of a florescent structure at a low excitation power 47 . The excited state lifetime of the observed single PbV center was estimated to be ~3.7 ns, which is consistent with another experimental result 31 . The fluorescence intensity is measured as a function of the excitation laser power, as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…To date, several studies have been reported for the fabrication of lead-vacancy (PbV) centers in diamond. However, the optical transition energy of the PbV center has not been determined consistently: values have been reported at ∼550 or ∼520 nm …”
mentioning
confidence: 99%
“…This is higher than but comparable to our previous work using solid metallic precursors, where a fluence of less than 1 x 10 12 cm -2 was needed to observe patterned regions of the same size. 19 The values obtained in this study are higher because of the lower concentration of adsorbates on the surface compared to a solid thin film and the ability for the gaseous precursors to desorb or diffuse unlike the solid metallic precursor. This naturally results in a lower probability of the recoil process, and therefore requires higher total fluence values.…”
Section: Resultsmentioning
confidence: 73%
“…13, Further to the above, we have recently demonstrated the use of recoil implantation [16][17][18] in combination with a standard FIB system. 19 In that work, momentum transfer from inert ions in a nano-scale beam to a thin film was used for implantation of the film constituents. This was demonstrated by implanting group IV elements into a bulk diamond substrate, which resulted in the creation of group IV color centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation